Understanding the Dynamics of Gender-Based Violence in Ivory Park Policing Area, Gauteng Province, South Africa: A Comprehensive Analysis - Sekgobela Hellen; Olutola Adewale; Mmakwena Modipa (Khazanah Hukum, 2023)
Gender-based violence (GBV) remains a pressing global concern, particularly pervasive in South Africa, where women and children often fall victim to its devastating impact. This article conducts a qualitative analysis of GBV in the Ivory Park Policing Area, utilizing a non-empirical research design through a systematic review of secondary data. The study identifies critical challenges within the criminal justice system's response to GBV and proposes key preventive measures. Recommendations include the imperative training of law enforcement officials in handling GBV cases, allocating resources to expedite case processing, and fostering stronger collaborations between the South African Police Service and various stakeholders. This research aims to contribute actionable insights for policymakers, law enforcement agencies, and community leaders to effectively combat and prevent GBV in the Ivory Park Policing Area.